The spatial analysis of FDI, R&D and economic growth in China - Minhua, Yuan; Ab-Rahim, Rossazana; Husaini, Dzul Hadzwan Bin (Asian Journal of Economic Modelling, 2026)
This study aims to examine the spatial spillover effects of foreign direct investment (FDI) and research and development (R&D) on China’s economic growth. Using panel data from 30 provinces between 2000 and 2022, the study applies spatial econometric models incorporating foreign trade openness, government expenditure, and population to capture interregional dynamics. The results reveal that both FDI and R&D significantly enhance provincial economic growth and exert positive spatial spillover effects on neighboring regions. Specifically, a 1% increase in FDI and R&D capital stock raises GDP by 0.02% and 0.05%, respectively, while interprovincial spillovers contribute 0.71% to the growth of adjacent provinces. These findings suggest that institutional innovation, regional cooperation, and the establishment of high-quality FDI-driven R&D centers are crucial to fostering a sustainable FDI–R&D–regional growth mechanism in China’s economy.